The Significance of Mining Infrastructural Development on South African Economy from 1980-2013: An Econometric Approach - Marutle, Ofentse William; Daw, Olebogeng David (Journal of Economics and Behavioral Studies, 2017)
In this present paper we investigate the relationship between mining infrastructure and economic growth in South Africa from 1980-2013. The importance of this paper is to examine if there is both short and long run significant relationship between mining infrastructure and economic growth in South Africa. The data mining was collected from South African Reserve Bank (SARB) covering the range from 1980-2013 of the paper. Both Augmented Dickey Fuller (ADF) and Phillip Perron (PP) where used for stationarity tests. Johansen Cointegration test is employed in this paper; also Vector Error Correction Model (VECM) is also employed in this paper. In the results we obtained that there is a positive significant relationship between mining infrastructure and economic growth. There is also a causal relationship between mining infrastructure and economic growth, meaning the development of mining infrastructure does promote economic growth. In conclusion the policy makers should improve private infrastructure which will equip human capital to be more useful in contributing towards knowledge and innovation. This means South African government and mining industry should priorities the development of infrastructure as component that will be sufficient towards economic development.